Meningkatkan Hasil Belajar Siswa Pada Pelajaran Geografis Materi Litamica Dinamik Melalui Kekuatan Dua Strategi di Kelas X SMA Negeri 3 Mawasangka - Arsad Rakunsi; La Ode Amaluddin (Universitas Negeri Makassar, 2019)
SMAN 3 Mawasangka is one of the schools in Buton Tengah Regency, Matara village which is the object of research by researchers because its learning outcomes are still low, this is because only 54% of them meet the KKM. The aims of this research are: 1. To find out the learning activities of X IPS class students by using power of two strategy and teacher teaching activities of SMAN 3 Mawasangka by using power of two strategy 2. To increase the student learning outcome on geographic subject on class X SMA Negeri 3 Mawasangka through the use of power of two. This study was conducted in class X IPS of SMAN 3 Mawasangka even semester 2018/2019 academic year, January 16 2019 until 16 February 2019. This type of research is classroom action research (CAR) conducted in two cycles. The subjects of this study were teachers and students of class X IPS SMAN 3 Mawasangka. Data in the study were qualitative and quantitative data obtained from observation sheets and learning outcomes tests. From the results of the analysis, it can be concluded that by applying the power of two strategy(1). Student learning activities increased with an average score of 3.1 categorized well. (2). Teacher teaching activities increased with an average score of 3.4 categorized well. (3). Geography learning outcomes of XI IPS class students at SMAN 3 Mawasangka increased with an average score of 77, with learning completeness of 83% or there were 20 students with a value of ≥ 72 according to KKM geography.SMAN 3 Mawasangka adalah salah satu sekolah di Kabupaten Buton Tengah Desa Matara yang menjadi objek penelitian peneliti karena hasil belajarnya yang masih rendah, hal ini disebabkan hanya 40% yang memenuhi KKM. Tujuan penelitian: (1)untuk mengetahui aktivitas belajar siswa kelas X IPS yang diajar dengan menggunakan strategy the power of two dan aktivitas mengajar guru SMAN 3 Mawasangka yang mengajar dengan menggunakan strategi the power of two,(2) untuk meningkatkan hasil belajar geografi siswa kelas X SMA Negeri 3 Mawasangka yang diajar dengan menggunakan strategi the power of two. Penelitian ini dilakukan dikelas X IPS SMAN 3Mawasangka semester genap tahun ajaran 2018/ 2019, tanggal 16 januari 2019 sampai dengan tanggal 16 February 2019. Jenis peneliitian adalah penelitian tindakan kelas (PTK) yang dilaksanakan dengan dua siklus.Subjek penelitian ini adalah guru dan siswa kelas X IPS SMAN 3 Mawasangka. Data dalam penelitian adalah data kualitatif dan kuantitatif yang diperoleh dari lembar observasi dan tes hasil belajar. Dari hasil analisis diperoleh kesimpulan bahwa dengan menerapkan strategy the power of two (1). Aktivitas belajar siswa meningkat dengan skor rata-rata 3,1 berkategorikan baik.(2). Aktivitas mengajar guru meningkat dengan skor rata-rata 3,4 berkategorikan baik.(3). Hasil belajar geografi siswa kelas X IPS SMAN 3 Mawasangka meningkat dengan skor rata-rata 77, dengan ketuntasan belajar 83% atau terdapat 20 siswa dengan nilai ≥ 72 sesuai KKM geografi.